Altered Functional Connectivity of Alpha Rhythm in Obsessive-Compulsive Disorder During Rest. (March 2019) - Tan, Bo; Liu, Qingxiao; Wan, Chaoyang; Jin, Zhenlan; Yang, Yanchun; Li, Ling
Obsessive-compulsive disorder (OCD) is a common inheritable psychiatric disorder characteristic of repetitive thinking, imagination (obsession), and stereotyped behaviors (compulsive). To explore whether there is an alteration of brain functional connectivity (BFC) in patients with OCD during rest, electroencephalogram (EEG) data of healthy controls (HCs) and patients with OCD were collected during rest in both eyes-closed and eyes-open states. Synchronization likelihood and graph theory were applied to construct and analyze brain functional networks of patients with OCD and HCs. Patients with OCD showed abnormal graph-theoretic parameters and impaired small world features in the alpha and beta bands. In addition, the topological analysis consistently showed that the long-range BFC of alpha rhythm was significantly reduced in the bilateral posterior areas in patients with OCD in comparison with HCs, while the BFC in the beta rhythm was significantly increased only in the eyes-open state. The findings suggest that the BFC of patients with OCD show abnormal small-world features and altered topological structure during rest, mainly in alpha and beta bands, which may provide a new insight for the diagnosis and treatment of OCD.